2006
DOI: 10.1002/mrc.1854
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and solvent dependent NMR studies on mangiferin and complete NMR spectral assignments of its acyl and methyl derivatives

Abstract: By employing concerted 1 and 2D NMR techniques, exact NMR spectral assignments have been made of the acyl (2-7) and methyl (8 and 9) derivatives of mangiferin (1) isolated from the leaves of Bombax ceiba. Derivatives 2, 8 and 9 have been reported in literature, while 3-7 represent new compounds. The acetates 2 and 3 were found to be unstable and were converted into the same penta-acetate 4 at room temperature. Extensive NMR studies on mangiferin (1) and its derivatives showed that H-4 exchanges with deuterium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 18 publications
3
25
0
Order By: Relevance
“…Rate constants of the H/D exchange of selected flavonols and flavones were H-NMR studies. This is the first time that H/D exchange during NMR studies was observed in patuletin (1) and patulitrin (2); previously this phenomenon was witnessed in the case of mangiferin (¼ 2-b-d-glucopyranosyl-1,3,6,7-tetrahydroxy-9H-xanthen-9-one), a xanthone C-glucoside, which is more related to flavonols than to xanthones [20]. Furthermore, the preparation of polydeuterated flavonoids and isoflavonoids was documented to allow identification and quantitation of these compounds in biological matrices [21a] [21b]; moreover, deuterated flavonoids have also been used for biosynthetic and metabolic study of flavonoids [21c].…”
mentioning
confidence: 81%
“…Rate constants of the H/D exchange of selected flavonols and flavones were H-NMR studies. This is the first time that H/D exchange during NMR studies was observed in patuletin (1) and patulitrin (2); previously this phenomenon was witnessed in the case of mangiferin (¼ 2-b-d-glucopyranosyl-1,3,6,7-tetrahydroxy-9H-xanthen-9-one), a xanthone C-glucoside, which is more related to flavonols than to xanthones [20]. Furthermore, the preparation of polydeuterated flavonoids and isoflavonoids was documented to allow identification and quantitation of these compounds in biological matrices [21a] [21b]; moreover, deuterated flavonoids have also been used for biosynthetic and metabolic study of flavonoids [21c].…”
mentioning
confidence: 81%
“…Methylated gum on hydrolysis has been found to yield 2,3,4,6-tetra-, 2,6-di-, and 2,4-di-o-methyl-D-galactose and 2,3,5-tri-and 2,5-di-o-methyl-L-arabinose (Faizi et al, 2006). Khan et al (2011) isolated and characterise a new flavone from the flower extract of Bombax ceiba using mass, NMR, IR and UV.…”
Section: Gumsmentioning
confidence: 99%
“…The 13 C NMR spectrum (Table 4) 163.1(H-1 0 /C-3) in the HMBC spectrum of 6 confirmed the C-C linkage between C-2 of the xanthone and C-1 of the sugar. Compound 6, mangiferin 2 0 ,3 0 ,4 0 ,5 0 -tetraacetate, has been prepared previously from mangiferin (Faizi et al, 2006) but the C-13 NMR spectrum is absent from the literature. That substance 7 was the tetramethoxy derivative of 6 was obvious from the 1 H and 13 C NMR spectra (Tables 3 and 4).…”
Section: Resultsmentioning
confidence: 99%
“…Since aerial parts of Hypericum canariense have been used as decoctions in the Canary Islands (Perez de Paz and Hernandez Padron, 1999) further investigation of the polar constituents of this species seemed warranted and we therefore attempted to establish the identity of biologically active constituent(s) from the water soluble fraction which had not been investigate previously. Isolated after acetylation of the complex mixture to permit more facile separation of the polar components and extensive chromatography were the new polyacetylated flavonol methyl glucopyranuronates 1-5, the known xanthone derivative 6 (mangiferin 2 0 ,3 0 ,4 0 ,6 0 -tetraacetate, Faizi et al, 2006) and the latter's new 1,3,6-trimethoxy-7-acetoxy-(8) and 1,7-diacetoxy-3,6-dimethoxy analog 9. We also encountered 1,3,6,7-tetramethoxy derivative 7 which has been prepared previously by partial synthesis (Aritomi and Kawasaki, 1970) although its characterization was sparse (Fig.…”
Section: Introductionmentioning
confidence: 99%